Molecular Mapping of Quantitative Trait Loci for Fusarium Head Blight Resistance in the Brazilian Spring Wheat Cultivar “Surpresa” - Poudel, Bikash; Mullins, Joseph; Puri, Krishna D.; Leng, Yueqiang; Karmacharya, Anil; Liu, Yuan; Hegstad, Justin; Li, Xuehui; Zhong, Shaobin (Frontiers in Plant Science, 2022)
Fusarium head blight (FHB) is a devastating disease in wheat. The use of resistant germplasm from diverse sources can significantly improve resistance to the disease. “Surpresa” is a Brazilian spring wheat cultivar with moderate FHB resistance, different from currently used sources. In this study, we aimed to identify and map the genetic loci for FHB resistance in Surpresa. A mapping population consisting of 187 recombinant inbred lines (RILs) was developed from a cross between Surpresa and a susceptible spring wheat cultivar, “Wheaton.” The population was evaluated for FHB by the point-inoculation method in three greenhouse experiments and four field trials between 2016 and 2018. Mean disease severity for Surpresa and Wheaton was 41.2 and 84.9% across the 3 years of experiments, ranging from 30.3 to 59.1% and 74.3 to 91.4%, respectively. The mean FHB severity of the NILs was 57%, with an overall range from 7 to 100%, suggesting transgressive segregation in the population. The population was genotyped using a two-enzyme genotyping-by-sequencing approach, and a genetic map was constructed with 5,431 single nucleotide polymorphism (SNP) markers. Four QTL for type II resistance were detected on chromosomes 3A, 5A, 6A, and 7A, explaining 10.4–14.4% of the total phenotypic variation. The largest effect QTL was mapped on chromosome 7A and explained 14.4% of the phenotypic variation; however, it co-localized with a QTL governing the days to anthesis trait. A QTL for mycotoxin accumulation was also detected on chromosome 1B, explaining 18.8% of the total phenotypic variation. The QTL for FHB resistance identified in the study may diversify the FHB resistance gene pool and increase overall resistance to the disease in wheat.